A harpa de pedais no século XVIII e as influências de suas características sobre seu repertório e escrita idiomática - Faglioni, Felipe [UNESP] (2015)
This paper aims to understand the conduct of the pedal harp and its music through the 18th century, and also to analyse its idiomatic writing which was common in the period, pointing its main characteristics and the particular mode how they are presented in the repertoire of the instrument from this time. The single-action harp, the instrument that was used during the mentioned period, presented characteristics which were unique and very different from those of the modern double-action harp, which is an invention from the beginning of the 19th century. Thus, the music composed for the instrument in the 18th century presented itself in a very peculiar way, reflecting the possibilities of the instrument then used. Throught historical and organological studies and through the analyses of methods and scores, this research intends to show important aspects of the single-action harp's idiomatic writing, also concerning relevant points involving the instrument, like its relation with the music's theory and practice during the time, its functions and visibility in the society and in the musical milieu and the work of composer and instrumentalists who were important to the harp's history and repertoire